Unsur-Unsur Surealisme dalam Puisi “Syaiun Sayabqa Bainana” Karya Faruq Juwaidah - Kamil, Moh (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2023)
This study aims to describe the elements of surrealism found in the poem "Syaiun Sayabqa Bainana. This study uses a constructivist research paradigm, while the research approach used in this study is a qualitative research approach in which this approach is in the form of information or data collected in the form of words, the analysis used in this study is based on logic. The technique of free association or the creation of other forms appears most often in Faruq Juwaidah's lover, who is forced to separate in order to obtain freedom. Because there are many forms of expression expressed by Faruq Juwaidah which have many other meanings outside of realism